The role of leadership in forming the culture of organisation favourable to knowledge management: case analysis - Vaitkevičius, Viktoras (Information & Media, 2017)
Among different societies, businesses and in the academic world, it is approved and declared that the 21st century is the era of knowledge economy and knowledge itself is one of the most powerful tools, used by organisations to maintain competitive advantage, improve business and the productivity of employees. One of the most prioritised tasks for organisational structures has become the strengthening of organisational abilities and making sure that knowledge management is effective as the organisation’s goals are being reached. Knowledge management itself cannot consolidate or prosper in an institution without human input, where, in this case, leadership takes a major part. Leadership applies direct influence to the organisational culture that is favourable to implementing and creating processes of knowledge management. It is almost impossible to make sure that knowledge is being shared without proper organisational culture. The essential task of leaders working in organisational structures in the context of knowledge management is to ensure such an environment in which members of the structure are motivated to acquire, develop, share and use knowledge for reaching common organisational goals. The article analyses the role of leadership in forming the knowledge management-friendly organisational culture, based on the results of empirical research made in the organisation of Lithuanian public sector.
Keywords: ...